Population Dynamics of Skipjack Tuna (Katsuwonus pelamis Linnaeus, 1758) Landed at Sadeng Coastal Fishing Port, Yogyakarta - Siswana, Atkha Devi; Saputra, Suradi Wijaya; Taufani, Wiwiet Teguh (Jurnal Laut Khatulistiwa, 2026)
Skipjack tuna (Katsuwonus pelamis) is a major fishery commodity landed at PPP Sadeng, Gunungkidul, Special Region of Yogyakarta, primarily caught using purse seine gear. This study aimed to determine the growth parameters, mortality and exploitation rates. A total of 1,428 randomly sampled fish were collected from June to September 2025. Growth parameters were analyzed using the von Bertalanffy model through the TropFishR in R Studio. Results showed an asymptotic length (L∞) of 75.4 cm, a growth coefficient (K) of 0.93 year⁻¹, t₀ of -0.13, and an isometric growth pattern (b= 3.0003). The length at first capture (Lc) was 44.02 cm. Total (Z), natural (M), and fishing (F) mortality rates were 2.31, 0.93, and 1.38 per year, respectively, with an exploitation rate (E) of 0.59, indicates a condition of potential overfishing.